Assessing whether serum ceruloplasmin promotes non-alcoholic steatohepatits via regulating iron metabolism - Sheng, Xiong; Xia, Ziqiang; Zheng, Liang; Zheng, Endian; Jin, Wenyi; Wu, Jinming (Journal of Medical Biochemistry, 2022)
Introduction: Non-alcoholic steatohepatitis (NASH) is a progressive form of non-alcoholic fatty liver disease (NAFLD). At present, the diagnostic gold standard for detecting NASH still relies upon an invasive pathological biopsy. There is therefore a need to identify non-invasive diagnostic markers. Oxidative stress mediates fatty liver progression to NASH. Imbalanced iron metabolism produces a large amount of reactive oxygen species (ROS). Ceruloplasmin is associated with oxidase and iron metabolism-related activities. The current study aimed to determine whether there was a correlation between ceruloplasmin levels and NASH, and whether such a relationship may be associated with altered iron metabolism in NASH patients.Materials and Methods: A total of 135 NAFLD patients were enrolled in this study, and a pathological biopsy confirmed that 60 of these patients had NAFLD activity scores (NAS) ≥ 5, while the remaining 75 had NAS < 5.Results: Receiver operating characteristic (ROC) curves confirmed that serum ceruloplasmin and ferritin levels were predictors of NAS ≥ 5 and NAS < 5, with area under the curve (AUC) values of 0.80 and 0.81, respectively. The serum ceruloplasmin levels in NAS ≥ 5 patients were significantly lower than those in NAS < 5 patients (p < 0.001). Serum ceruloplasmin levels were also negatively correlated with ferritin levels, and lower serum ceruloplasmin levels were associated with more severe histopathological findings.Conclusion: Low serum ceruloplasmin and high serum ferritin are correlated with NASH, and low serum ceruloplasmin may be associated with NASH owing to its ability to increase iron load.
Keywords: Ceruloplasmin; Ferritin; Non-alcoholic fatty liver disease; Non-alcoholic steatohepatitis